Financial inclusion across Asia : bringing opportunities for businesses - Choi-Meng, Leong; Ali, Muhammad; Raza, Syed Ali; Puah, Chin-Hong; Eksi, Ibrahim Halil (Emerald Publishing Limited, 2023)
The term financial inclusion describes an individual's ability to obtain effective and inexpensive financial products and services that match their demands, whilst extending to include businesses access to finances to enable planning for long-term goals or unpredictable emergencies. This allows micro, small, and medium-sized businesses to access financial products on a sustainable basis for a reasonable price. Financial Inclusion Across Asia provides thought-provoking studies centred around Asia and the United Nations Sustainable Development Goals (SDGs). Some of the many topics discussed in this collection include financial inclusion in under-served markets, financial inclusion products and services, financial inclusion for sustainable and responsible business, micro, small, and medium-sized business practices. The chapter authors consider Artificial Intelligence, Block Chain and Robotics in financial inclusion for businesses, and financial inclusion in the Industrial Revolution (IR) 4.0. This collection of studies is useful for social scientists, students, academicians, academic institutions, policymakers, and other related stakeholders. It is also appropriate for practitioners or financial sector stakeholders to discover potential business opportunities of financial inclusion products and services, allowing them to strategically incorporate the SDGs.
Includes index.
Keywords: Business enterprises -- Asia.; Business & Economics -- Business Ethics.; Business ethics & social responsibility.; elektronické knihy; electronic books